К вопросу об аллофонических изменениях - Воронкова, Г. В.; Лепкова, Л. Н. (Kalbotyra, 1985)
The article deals with the problem of reconstruction of phonological mutations. It is pointed out that changes in distribution of allophones usually forego phonemic mutation. This fact determines necessity of reconstruction of allophonic stages in diachronic researches. The fruitfulness of this method is shown by such reconstructions in West and North German languages.